An analysis of the turn-of-the-year effect in South African equity returns - Potgieter, Damien (Rhodes University, Faculty of Commerce, Department of Economics, 2007)
This study investigates FTSE/JSE All Share index monthly and daily equity returns for evidence of the January and TY effect. Four different measures of monthly return are analysed for the 1995-2006 period, whilst daily returns are analysed during the 1995-2005 period. In addition to this, analysis is conducted on monthly Fama-MacBeth risk premium estimates tor the FTSE/JSE All Share Index. Descriptive statistics are first analysed, followed by ANOV A or Kruskai-Wallis tests, the paired t-test and finally dummy variable regression analysis in investigating the seasonality of FTSE/JSE All Share Index returns and risk premia. Analysis on monthly returns reveals an absence of the January effect, however a positive slightly statistically significant December effect is found. Thus, investors earn abnormal returns on equity during the month of December. The results from the Fama-MacBeth risk premia estimates reveals highly statistically significant negative risk premia seasonal patterns during March, July and September. Thus, investors are in fact penalised for investing in equities during these months. In addition, the analysis reveals an absence of a December effect in risk premia, which contradicts the risk-return trade-off central to modem finance. The daily return analysis reveals a highly significant Turn-of-the-Year effect (TY), which suggests that investors earn abnormal returns on days at the turn of the year. Therefore, it is concluded that a December effect is apparent in South African equity monthly returns, whilst a March, July and September effect is apparent in South African equity risk premia contradicting the risk-return trade-off central to modem finance. In addition to this, a TY effect is present in South African equity daily returns.
Keywords: Johannesburg Stock Exchange; FTSE International; Stock exchanges -- South Africa; Stock price indexes -- South Africa